Cophylogenetic assessment of New World warblers (Parulidae) and their symbiotic feather mites (Proctophyllodidae). (15th March 2018) - Matthews, Alix E.; Klimov, Pavel B.; Proctor, Heather C.; Dowling, Ashley P. G.; Diener, Lizzie; Hager, Stephen B.; Larkin, Jeffery L.; Raybuck, Douglas W.; Fiss, Cameron J.; McNeil, Darin J.; Boves, Than J.
Abstract : Host–symbiont relationships are ubiquitous in nature, yet evolutionary and ecological processes that shape these intricate associations are often poorly understood. All orders of birds engage in symbioses with feather mites, which are ectosymbiotic arthropods that spend their entire life on hosts. Due to their permanent obligatory association with hosts, limited dispersal and primarily vertical transmission, we hypothesized that the cospeciation between feather mites and hosts within one avian family (Parulidae) would be perfect (strict cospeciation). We assessed cophylogenetic patterns and tested for congruence between species in two confamiliar feather mite genera (Proctophyllodidae: Proctophyllodes, Amerodectes ) found on 13 species of migratory warblers (and one other closely related migratory species) in the eastern United States. Based on COI sequence data, we found three Proctophyllodes lineages and six Amerodectes lineages. Distance‐ and event‐based cophylogenetic analyses suggested different cophylogenetic trajectories of the two mite genera, and although some associations were significant, there was little overall evidence supporting strict cospeciation. Host switching is likely responsible for incongruent phylogenies. In one case, we documented prairie warblers Setophaga discolor harboring two mite species of the same genus. Most interestingly, we found strong evidence that host ecology may influence the likelihood of host switching occurring. For example, we documented relatively distantly related ground‐nesting hosts (ovenbird Seiurus aurocapilla and Kentucky warbler Geothlypis formosa ) sharing a single mite species, while other birds are shrub/canopy or cavity nesters. Overall, our results suggest that cospeciation is not the case for feather mites and parulid hosts at this fine phylogenetic scale, and raise the question if cospeciation applies for other symbiotic systems involving hosts that have complex life histories. We also provide preliminary evidence that incorporating host ecological traits into cophylogenetic analyses may be useful for understanding how symbiotic systems have evolved.